Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$\lim_{n \to \infty}{\frac{1^1+2^2+3^3+\cdots+n^n}{n^n}}.$$

With a first look this must give $1$ as a result but have a problem to explain it.

How can I do it?


I noticed that it is $\frac{\infty}{\infty}$.

$$\lim_{n \to \infty}{n^{n}\frac{(\frac{1^1}{n^{n}}+\frac{2^2}{n^{n}}+\frac{3^3}{n^{n}}+\cdots+1)}{n^n}}= \lim_{n \to \infty}{\frac{1^1}{n^{n}}+\frac{2^2}{n^{n}}+\frac{3^3}{n^{n}}+\cdots+1}=1$$

Is this correct?

share|cite|improve this question
I improved the TeXing a bit. It seemed that you were missing $n \to \infty$ in the question, so I took the liberty to add it. – Srivatsan Oct 29 '11 at 19:57
Why is the last limit 1? You have a 1 and $n-1$ terms which converge to 0, so when you take the limit you get one + infinitely many zeros. The answer can still be anything.... – N. S. Oct 29 '11 at 21:32
So you say that the actual result is $0\cdot\infty+1$ and this is undefined. – ertzan topal Oct 29 '11 at 21:38

4 Answers 4

up vote 20 down vote accepted

We can write $(1^1+2^2+\cdots+n^n)/n^n$ as $a_n + b_n + 1$, where $$ a_n = \frac{1^1+2^2+\cdots+(n-2)^{n-2}}{n^n} \text{ and } b_n = \frac{(n-1)^{n-1}}{n^n}. $$ Both $a_n$ and $b_n$ are positive, and also $$ a_n < \frac{(n-2)(n-2)^{n-2}}{n^n} < b_n < \frac{n^{n-1}}{n^n} = \frac1n. $$ The squeeze theorem should allow you to prove that your answer of 1 is correct.

share|cite|improve this answer
We can't just apply del Hospital rule? It is $\frac{\infty}{\infty}$. – ertzan topal Oct 29 '11 at 20:23
What's the derivative of the numerator as $n \to \infty$? To find that you'd need to find a way to interpret the numerator when $n$ is not an integer. – Michael Lugo Oct 29 '11 at 20:47
@Chris: since we want the quantity $a_n+b_n+1$ to tend to $1$ in the limit, it's important to have a diminishing upper bound like $b_n < 1/n$. – Greg Martin May 28 '12 at 22:26

I know I'm terribly late, but I'd like to post a similar but a bit different from Micheal and Greg's approach. Plese tell me in the comments if it's not sufficiently different.

Let $$a_n=\frac{1^1+2^2+3^3+\cdots+(n-1)^{n-1}}{n^n}. $$ So we have $$a_{n+1}=\frac{1^1+2^2+3^3+\cdots+(n-1)^{n-1}+n^n}{(n+1)^{n+1}}=\frac{n^n(a_n+1)}{(n+1)^{n+1}}$$ and thus $$\lim_{n\to\infty}a_n=\lim_{n\to\infty}\frac{a_nn^n}{(n+1)^{n+1}}+\frac{n^n}{(n+1)^{n+1}}=\lim_{n\to\infty}\frac{a_nn^n}{(n+1)^{n+1}}.\tag{1}$$ Since $$\lim_{n\to\infty}\frac{n^n}{(n+1)^{n+1}}=0,$$ $(1)$ yields that $a_n$ either converges to $0$ or diverges to $+\infty$. But $$\lim_{n\to\infty}a_n\le\lim_{n\to\infty}\frac{\overbrace{(n-1)^{n-1}+(n-1)^{n-1}+\cdots+(n-1)^{n-1}}^{n-1 \ \text{times}}}{n^n}=\lim_{n\to\infty}\frac{(n-1)^n}{n^n}=e^{-1}, $$ hence $$\lim_{n\to\infty}a_n=0,$$ which allows us to conclude $$\lim_{n\to\infty}\frac{1^1+2^2+3^3+\cdots+n^n}{n^n}=1.$$

share|cite|improve this answer

Stolz-Cesàro is probably overkill, but solves the problem easily.

The limit

$$\lim\limits_{n\to\infty} \frac{(n+1)^{n+1}}{(n+1)^{n+1}-n^n} =1 \,,$$ is very simple to calculate.

share|cite|improve this answer

Let $f(n) = (1^1 + 2^2 + 3^3 + \cdots + n^n)/n^n$. You want to show $\lim_{n \to \infty} f(n) = 1$.

It's obvious that $f(n) > 1$ for all $n$.

For an upper bound, $$ f(n) \le {1^{n-2} + 2^{n-2} + \cdots + (n-2)^{n-2} \over n^n} + {n^{n-1} \over n^n} + {n^n \over n^n} = {1^{n-2} + 2^{n-2} + \cdots + (n-2)^{n-2} \over n^n} + {1 \over n} + 1.$$

Now I leave it to you to find some bound $g(n)$, with $\lim_{n \to \infty} g(n) = 0$ and $$ {1^{n-2} + 2^{n-2} + \cdots + (n-2)^{n-2} \over n^n} \le g(n). $$ So you have $$ 1 < f(n) < 1 + {1 \over n} + g(n) $$ and apply the squeeze theorem to finish the proof.

share|cite|improve this answer
ha, you beat me by 45 seconds! – Greg Martin Oct 29 '11 at 20:02

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.